A method for characterizing the crystalline quality of a 3C-SiC epitaxial layer and a method for characterizing the crystalline quality of a 3C-SiC substrate

CN118980700BActive Publication Date: 2026-10-16SICC SHANGHAI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411193275.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2026-10-16
Estimated Expiration
2044-08-28

AI Technical Summary

Technical Problem

这种衍射角度下的穿透深度在30μm左右,50μm以下,因此在测试过程中无法区分外延层3C-SiC和4H-SiC,无法表征3C-SiC外延层的结晶质量

Benefits of technology

[0040]1. The method for characterizing the crystal quality of 3C-SiC epitaxial layer in this application uses (112) and (113) crystal planes for testing. The incident angle is small and the penetration depth of X-rays is shallow, which can characterize the crystal quality of 3C-SiC epitaxial layer. Moreover, the signal of the substrate 4H-SiC will not be detected, and the test accuracy and reliability are high.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118980700B_ABST
    Figure CN118980700B_ABST
Patent Text Reader

Abstract

The application discloses a method for characterizing the crystallization quality of a 3C-SiC epitaxial layer and a method for characterizing the crystallization quality of a 3C-SiC substrate, and belongs to the technical field of 3C-SiC material quality characterization. The method comprises the following steps: (1) placing a polished 3C-SiC epitaxial layer or a 3C-SiC substrate on a sample table of an X-ray diffractometer; (2) performing diffraction test on the (112) crystal face and the (113) crystal face of the 3C-SiC epitaxial layer or the 3C-SiC substrate by using X-rays to obtain the half-height width, respectively; when the difference between the half-height width of the (113) crystal face and the half-height width of the (112) crystal face is not greater than 40 arcsec, the half-height width of the (112) crystal face and the half-height width of the (113) crystal face are the crystallization quality parameters of the 3C-SiC epitaxial layer or the 3C-SiC substrate. The method can realize quantitative characterization of the crystallization quality of the 3C-SiC epitaxial layer and the 3C-SiC substrate, and can play a guiding role in the optimization of the 3C-SiC material growth process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to a method for characterizing the crystal quality of a 3C-SiC epitaxial layer and a method for characterizing the crystal quality of a 3C-SiC substrate, belonging to the field of 3C-SiC material quality characterization technology. Background Technology

[0002] Silicon carbide materials possess excellent electrical and optical properties, leading to their increasing commercialization in recent years. However, silicon carbide has over 200 crystal forms, each with different symmetries and interatomic spacings, resulting in variations in its physical properties.

[0003] Currently, the most researched silicon carbide crystals are the 4H and 6H forms, both of which are hexagonal. Silicon carbide, however, only has one cubic structure: the 3C form. Compared to hexagonal silicon carbide, 3C-SiC exhibits higher carrier mobility and saturation velocity. Furthermore, this form is stable at around 1500℃, requiring a lower growth temperature and making it easier to mass-produce. Therefore, it may have wide applications in next-generation devices.

[0004] Currently, the growth of 3C-SiC mainly involves heteroepitaxial growth using 4H-SiC as a substrate to obtain 3C-SiC epitaxial layers. However, heteroepitaxial growth presents several potential problems, such as the emergence of double-positioning boundary defects, or the difficulty in achieving a growth thickness exceeding 50 μm. These issues make it challenging to characterize the crystal quality and symmetry using conventional methods.

[0005] According to the principle of minimizing lattice mismatch, the surface of the 3C-SiC epitaxial layer grown by heteroepitaxial growth is the (111) plane. The conventional method for characterizing crystallization is to test the rocking curve using an X-ray diffractometer, that is, the half-width at half-maximum (WHM) of the diffraction peak at a specific diffraction angle. However, the incident angle of the (111) plane of 3C-SiC under X-ray diffraction is 17.8°, and the incident angle of the (004) plane of 4H-SiC is also about 17.8°. The penetration depth at this diffraction angle is about 30 μm and below 50 μm. Therefore, it is impossible to distinguish between the epitaxial layers 3C-SiC and 4H-SiC during the test, and it is impossible to characterize the crystal quality of the 3C-SiC epitaxial layer.

[0006] Similarly, the substrate of 3C-SiC also has a (111) crystal plane. Since 3C-SiC has poorer stiffness than 4H-SiC, it is necessary to polish it multiple times and test it in order to obtain more accurate crystal quality, but this can easily cause the substrate to crack.

[0007] Furthermore, due to the similarity of the building blocks of 4H-SiC and 3C-SiC, conventional XRD characterization methods are insufficient to determine whether the 3C-SiC epitaxial layer exhibits a single crystal form. Therefore, understanding how to characterize the 3C-SiC epitaxial layer and the 3C-SiC substrate is crucial for optimizing subsequent growth processes. Summary of the Invention

[0008] To address the aforementioned issues, a method for characterizing the crystal quality of a 3C-SiC epitaxial layer and a method for characterizing the crystal quality of a 3C-SiC substrate are provided. This method employs X-ray diffraction testing on the (112) and (113) crystal planes of the 3C-SiC epitaxial layer or the 3C-SiC substrate, and uses the full width at half maximum (FWHM) obtained from the two crystal planes to compare and verify the accuracy of the testing method. This method enables quantitative characterization of the crystal quality of the 3C-SiC epitaxial layer and the 3C-SiC substrate, and can provide guidance for optimizing the 3C-SiC material growth process.

[0009] According to one aspect of this application, a method for characterizing the crystallinity quality of a 3C-SiC epitaxial layer is provided, comprising the following steps:

[0010] (1) Place the polished 3C-SiC epitaxial layer on the sample stage of the X-ray diffractometer;

[0011] (2) The half-width at half maximum (WHM) of the (112) and (113) crystal planes of the 3C-SiC epitaxial layer is obtained by X-ray diffraction test. When the difference between the WHM of the (113) crystal plane and the WHM of the (112) crystal plane is not greater than 40 arcsec, the WHM of the (112) crystal plane and the WHM of the (113) crystal plane are the crystal quality parameters of the 3C-SiC epitaxial layer.

[0012] Based on the characteristics of different crystal planes of 3C-SiC, at the same test location of the same 3C-SiC epitaxial layer, the full width at half maximum (FWHM) value obtained by the (113) crystal plane is greater than that obtained by the (112) crystal plane. Therefore, when the difference between the FWHM values ​​of the two crystal planes is no greater than 40 arcsec, it means that the characterization method is correct. This difference refers to the FWHM value of the (113) crystal plane minus the FWHM value of the (112) crystal plane.

[0013] When using the (111) crystal plane to characterize the crystal quality of the 3C-SiC epitaxial layer, firstly, it is easy to introduce the signal of the 4H-SiC substrate, which leads to inaccurate test results; secondly, the surface state of the 3C-SiC epitaxial layer after polishing will affect the test results, and multiple polishing corrections of the 3C-SiC epitaxial layer are required to obtain better results, but multiple polishings will make the thickness of the 3C-SiC epitaxial layer not meet the requirements.

[0014] Therefore, this application uses the (112) and (113) crystal planes to characterize the crystal quality of the 3C-SiC epitaxial layer, which can solve the above problems. Furthermore, the crystal quality data obtained from the (112) and (113) crystal plane tests are crystal quality data within the 3C-SiC epitaxial layer, which are more reflective of the overall crystal quality than the test data from the (111) crystal plane. The smaller the difference between the full width at half maximum (FWHM) of the (113) crystal plane and the FWHM of the (112) crystal plane, the better the crystal quality of the 3C-SiC epitaxial layer.

[0015] Optionally, the polishing in step (1) uses zirconium oxide as an abrasive. Since the Mohs hardness of zirconium oxide is around 8.5, which is close to that of 3C-SiC, and zirconium oxide is more wear-resistant, it can be reused, thus reducing costs.

[0016] Optionally, in step (2), the incident angle of the X-ray diffraction test on the (112) crystal plane of the 3C-SiC epitaxial layer is 10.6°±0.5° and the exit angle is 30.07°±0.5°.

[0017] Optionally, in step (2), the incident angle of the X-ray diffraction test on the (113) crystal plane of the 3C-SiC epitaxial layer is 6.36°±0.5° and the exit angle is 35.87°±0.5°.

[0018] The two crystal planes mentioned above have small incident angles and shallow test depths, about 8 μm, which are suitable for characterizing epitaxial layers without testing the signal of the 4H-SiC substrate. The incident angle of the (112) crystal plane has a deeper penetration depth than that of the (113) crystal plane, but its penetration depth will not exceed 10 μm, so it is still suitable for characterizing the crystal quality of 3C-SiC epitaxial layers.

[0019] Optionally, the surface warp value of the polished 3C-SiC epitaxial layer is less than 20 μm.

[0020] Optionally, the scanning range of planes (112) and (113) in step (2) is no greater than 2000 arcsec. Diffraction tests are performed within 2000 arcsec, and the obtained test data have no impurity peaks except for the main peak, which indicates that the 3C-SiC epitaxial layer has a single crystal form.

[0021] Optionally, the diameter of the 3C-SiC epitaxial layer is 6 inches or more, preferably 8 inches or more.

[0022] Optionally, in step (2), at least 5 tests are performed on both the (112) and (113) crystal planes.

[0023] According to another aspect of this application, a method for characterizing the crystal quality of a 3C-SiC substrate is provided, comprising the following steps:

[0024] (1) Place the polished 3C-SiC substrate on the sample stage of the X-ray diffractometer;

[0025] (2) The half-width at half maximum (WHM) of the (112) and (113) crystal planes of the 3C-SiC substrate is obtained by X-ray diffraction test. When the difference between the WHM of the (113) crystal plane and the WHM of the (112) crystal plane is not greater than 40 arcsec, the WHM of the (112) crystal plane and the WHM of the (113) crystal plane are the crystal quality parameters of the 3C-SiC substrate.

[0026] Although 3C-SiC substrates do not have the interference factors of 4H-SiC substrates, the test data for crystal quality characterization using the (111) crystal plane is still affected by surface undulations, requiring repeated polishing corrections to overcome this. However, repeated polishing can lead to insufficient thickness of the 3C-SiC substrate and easily cause crystal cracking. Therefore, characterization of the (112) and (113) crystal planes is used to solve this problem. Furthermore, the crystal quality data obtained from testing the (112) and (113) crystal planes are internal crystal quality data of the 3C-SiC substrate, which better reflects the overall crystal quality compared to the test data of the (111) crystal plane. The smaller the difference between the full width at half maximum (FWHM) of the (113) crystal plane and the FWHM of the (112) crystal plane, the better the crystal quality of the 3C-SiC substrate.

[0027] Optionally, the polishing in step (1) uses zirconium oxide as an abrasive. Since the Mohs hardness of zirconium oxide is around 8.5, which is close to that of 3C-SiC, and zirconium oxide is more wear-resistant, it can be reused, thus reducing costs.

[0028] Optionally, in step (2), the incident angle of the X-ray diffraction test on the (112) crystal plane of the 3C-SiC substrate is 10.6°±0.5° and the exit angle is 30.07°±0.5°.

[0029] Optionally, in step (2), the incident angle of the X-ray diffraction test on the (113) crystal plane of the 3C-SiC substrate is 6.36°±0.5° and the exit angle is 35.87°±0.5°.

[0030] Optionally, the surface warpage of the polished 3C-SiC substrate is less than 20 μm.

[0031] Optionally, the scanning range of planes (112) and (113) in step (2) is no greater than 2000 arcsec. Diffraction tests are performed within 2000 arcsec, and the obtained test data have no impurity peaks except for the main peak, which indicates that the 3C-SiC substrate has a single crystal form.

[0032] Optionally, the diameter of the 3C-SiC substrate is 6 inches or more, preferably 8 inches or more.

[0033] Optionally, in step (2), at least 5 tests are performed on both the (112) and (113) crystal planes.

[0034] The above 5 test points should be at least (-65,0), (65,0), (0,65), (0,-65) and (0,0).

[0035] Preferably, in step (2), at least 9 tests are performed on both the (112) and (113) crystal planes.

[0036] The above 9 test points are at least (-85,0), (85,0), (0,85), (0,-85), (-40,0), (40,0), (0,40), (0,-40), and (0,0).

[0037] Optionally, the polishing removal thickness of the 3C-SiC epitaxial layer and the 3C-SiC substrate should not exceed 1 μm. Since the thickness of the 3C-SiC epitaxial layer is typically between 10-50 μm, preferably 30-50 μm, a polishing removal thickness of less than 1 μm ensures the integrity of the 3C-SiC epitaxial layer, reduces losses, and prevents cracking due to excessive removal. Although the thickness of the 3C-SiC substrate is thicker than that of the 3C-SiC epitaxial layer, typically 300-500 μm, excessive removal can easily cause cracking of the 3C-SiC substrate. Therefore, the polishing removal thickness of the 3C-SiC substrate should also not exceed 1 μm. After polishing, the surface warpage of the 3C-SiC epitaxial layer and the 3C-SiC substrate is less than 20 μm, which can further improve the accuracy of the detection results.

[0038] Based on the characteristic

[111] crystal orientation of 3C-SiC, this application uses the (112) and (113) crystal planes as the diffraction test planes, which allows the

[111] crystal orientation of 3C-SiC to be projected onto the exact center of the (112) and (113) crystal planes, facilitating accurate acquisition of the crystal quality information of 3C-SiC. Furthermore, since the (112) crystal plane is closer to the cleavage plane, the full width at half maximum (FWHM) value obtained by the (113) crystal plane is higher than that of the (112) crystal plane, indicating a slightly lower crystal quality. However, this application uses the (112) crystal plane for testing and the (113) crystal plane for verification, or vice versa, which allows the test parameters of the (112) crystal plane to be mutually verified with those of the (113) crystal plane, thus proving that the characterization method of this application is accurate and effective.

[0039] The beneficial effects of this application include, but are not limited to:

[0040] 1. The method for characterizing the crystal quality of 3C-SiC epitaxial layer in this application uses (112) and (113) crystal planes for testing. The incident angle is small and the penetration depth of X-rays is shallow, which can characterize the crystal quality of 3C-SiC epitaxial layer. Moreover, the signal of the substrate 4H-SiC will not be detected, and the test accuracy and reliability are high.

[0041] 2. The method for characterizing the crystal quality of the 3C-SiC epitaxial layer and the 3C-SiC substrate in this application can simultaneously test the (112) crystal plane and the (113) crystal plane to mutually verify the accuracy of the test method. Moreover, the two crystal planes can more comprehensively characterize the crystal quality of the epitaxial layer or the substrate, thereby providing guidance for subsequent optimization of the growth process.

[0042] 3. The method for characterizing the crystal quality of the 3C-SiC epitaxial layer and the 3C-SiC substrate in this application can be completed without tilting the sample stage of the X-ray diffractometer. Therefore, the sample stability is high during the test, which can further improve the accuracy of the test results.

[0043] 4. The method for characterizing the crystal quality of the 3C-SiC epitaxial layer and the 3C-SiC substrate in this application is convenient and quick to test, with a short testing time, and will not damage the 3C-SiC epitaxial layer and the 3C-SiC substrate. It belongs to non-destructive testing and is suitable for widespread use. Attached Figure Description

[0044] The accompanying drawings, which are included to provide a further understanding of this application and form part of this application, illustrate exemplary embodiments and are used to explain this application, but do not constitute an undue limitation of this application. In the drawings:

[0045] Figure 1 This is a schematic diagram of the microscopic model of 3C-SiC.

[0046] Figure 2 This is a test schematic diagram for determining the emission angle of the (112) crystal plane involved in Embodiment 1 of this application.

[0047] Figure 3 This is a test schematic diagram for determining the emission angle of the (113) crystal plane involved in Embodiment 2 of this application.

[0048] Figure 4 This is a test schematic diagram for determining the emission angle of the (111) crystal plane involved in Embodiment 3 of this application. Detailed Implementation

[0049] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.

[0050] Unless otherwise specified, the 3C-SiC epitaxial layer or 3C-SiC substrate in the embodiments of this application are prepared by conventional methods or purchased through commercial channels.

[0051] Unless otherwise specified, the methods used in the embodiments of this application are conventional methods in the prior art.

[0052] Figure 1 This is a schematic diagram of the microscopic model of 3C-SiC, where the blue line represents the (112) crystal plane and the pink line represents the (113) crystal plane. The following examples test the silicon carbide crystal quality of the two crystal planes.

[0053] Example 1

[0054] This embodiment relates to the determination of the incident angle and the exit angle when performing diffraction tests on the (112) crystal plane in a 3C-SiC epitaxial layer.

[0055] In this embodiment, the incident angle of the (112) crystal plane was first determined to be 10.6° by calculation. Then, the exit angle was changed to determine the range of the exit angle when the strongest diffraction peak was present. The results are shown in [the table below]. Figure 2 Therefore, the emission angle of the (112) crystal plane is determined to be 30.07°±0.5°.

[0056] Based on the same testing principle, the exit angle of the (112) crystal plane was first determined to be 30.07°. Then, the incident angle was changed to determine the angle range of the incident angle when the strongest diffraction peak was present. The exit angle of the (112) crystal plane was determined to be 10.6°±0.5°.

[0057] Example 2

[0058] This embodiment relates to the determination of the incident angle and the exit angle when performing diffraction tests on the (113) crystal plane in a 3C-SiC epitaxial layer.

[0059] In this embodiment, the incident angle of the (113) crystal plane was first determined to be 6.36° by calculation. Then, the exit angle was changed to determine the range of the exit angle when the strongest diffraction peak was present. The results are shown in [the table below]. Figure 3 Therefore, the emission angle of the (112) crystal plane is determined to be 35.87°±0.5°.

[0060] Based on the same testing principle, the exit angle of the (113) crystal plane was first determined to be 35.87°. Then, the incident angle was changed to determine the angle range of the incident angle when the strongest diffraction peak was present. The exit angle of the (113) crystal plane was determined to be 6.36°±0.5°.

[0061] Example 3

[0062] This embodiment relates to the determination of the incident angle and exit angle when performing diffraction tests on the (111) crystal plane in a 3C-SiC epitaxial layer.

[0063] In this embodiment, the incident angle of the (111) crystal plane was first determined to be 17.8° by calculation. Then, the exit angle was changed to determine the range of exit angles when the strongest diffraction peak was present. The results are shown in [the table below]. Figure 4 It can be seen that when the (111) crystal plane is used to test the 3C-SiC epitaxial layer, the range of its emission angle is relatively large, roughly in the range of 35°-36.5°, and there are two main peaks, proving that the signals of 3C-SiC, 4H-SiC and lattice mismatch will be detected.

[0064] Example 4

[0065] This embodiment relates to a method for characterizing the crystal quality of a 6-inch 3C-SiC epitaxial layer, which includes both a 4H-SiC substrate and 3C-SiC formed on the surface of the 4H-SiC substrate, and includes the following steps:

[0066] (1) The polished 3C-SiC epitaxial layer was placed on the sample stage of the X-ray diffractometer. The surface warp value of the polished 3C-SiC epitaxial layer was less than 20 μm.

[0067] (2) Five-point diffraction tests were performed on the (112) and (113) crystal planes of the 3C-SiC epitaxial layer using X-rays to obtain the full width at half maximum (FWHM). The incident angle for the diffraction test of the (112) crystal plane was 10.6°, and the exit angle is shown in Table 1. The incident angle for the diffraction test of the (113) crystal plane was 6.36°, and the exit angle is shown in Table 1. The scanning range of the (112) and (113) planes was no greater than 2000 arcsec. The test results of the FWHM of the two crystal planes are shown in Table 1.

[0068] Furthermore, for the same 3C-SiC epitaxial layer, a 5-point diffraction test was performed on the (111) crystal plane as a control test. The incident angle of the (111) crystal plane diffraction test was 17.8°. The test results of the (111) crystal plane half width at half maximum (FWHM) are shown in Table 1.

[0069] Table 1

[0070]

[0071] According to the test results in Table 1, the difference between the full width at half maximum (FWHM) of the (113) crystal plane and the FWHM of the (112) crystal plane is no greater than 40 arcsec. Therefore, the FWHM of the (112) crystal plane and the FWHM of the (113) crystal plane are the crystal quality parameters of the 3C-SiC epitaxial layer. The large fluctuation in the FWHM data of the (111) crystal plane proves that it is easy to introduce the 4H-SiC signal at the test point. Furthermore, the difference between the FWHM of the (112) crystal plane and the (111) crystal plane is greater than 90 arcsec, and the difference between the FWHM of the (113) crystal plane and the (111) crystal plane is greater than 60 arcsec. This proves that using the (111) crystal plane to test the 3C-SiC epitaxial layer easily introduces the 4H-SiC test signal, thus failing to accurately characterize the crystal quality of the 3C-SiC epitaxial layer.

[0072] Example 5

[0073] This embodiment relates to a method for characterizing the crystal quality of an 8-inch 3C-SiC substrate, which is prepared using conventional methods, and includes the following steps:

[0074] (1) Place the polished 3C-SiC substrate on the sample stage of the X-ray diffractometer. The surface Warp value of the polished 3C-SiC substrate is less than 20 μm.

[0075] (2) The full width at half maximum (FWHM) of the (112) and (113) crystal planes of the 3C-SiC substrate were obtained by performing 9-point diffraction tests using X-rays. The incident angle for the diffraction test of the (112) crystal plane was 10.6°, and the exit angle is shown in Table 2. The incident angle for the diffraction test of the (113) crystal plane was 6.36°, and the exit angle is shown in Table 2. The scanning range of the (112) and (113) planes was no greater than 2000 arcsec. The test results of the FWHM of the two crystal planes are shown in Table 2.

[0076] Furthermore, for the same 3C-SiC substrate, a 9-point diffraction test was performed on the (111) crystal plane as a control test. The incident angle of the (111) crystal plane diffraction test was 17.8°. The test results of the (111) crystal plane half-width are shown in Table 2.

[0077] Table 2

[0078]

[0079]

[0080] According to the test results in Table 2, the difference between the full width at half maximum (FWHM) of the (113) crystal plane and the FWHM of the (112) crystal plane of the 3C-SiC substrate is no greater than 40 arcsec, which proves that the method of this embodiment can characterize the crystal quality of the 3C-SiC substrate. Therefore, the FWHM of the (112) crystal plane and the FWHM of the (113) crystal plane are the crystal quality parameters of the 3C-SiC epitaxial layer. According to the test data of the (111) crystal plane, although the 3C-SiC substrate does not introduce the test signal of the 4H-SiC substrate when the (111) crystal plane is used for testing, the full width at half maximum (FWHM) data obtained at different test points are very different. This proves that the (111) crystal plane is affected by the surface undulation of the substrate, which leads to a decrease in detection accuracy. In order to improve the detection accuracy, multiple polishing corrections are required. However, the 3C-SiC substrate after multiple polishing corrections cannot meet the requirements. Therefore, the (111) crystal plane cannot be used to accurately characterize the crystal quality of the 3C-SiC substrate.

[0081] Example 6

[0082] This embodiment relates to a method for characterizing the crystal quality of a 6-inch 3C-SiC substrate, which is prepared using conventional methods, and includes the following steps:

[0083] (1) Place the polished 3C-SiC substrate on the sample stage of the X-ray diffractometer. The surface Warp value of the polished 3C-SiC substrate is less than 20 μm.

[0084] (2) Five-point diffraction tests were performed on the (112) and (113) crystal planes of the 3C-SiC substrate using X-rays to obtain the full width at half maximum (FWHM). The incident angle for the diffraction test of the (112) crystal plane was 10.1°, and the exit angle is shown in Table 3. The incident angle for the diffraction test of the (113) crystal plane was 5.86°, and the exit angle is shown in Table 3. The scanning range of the (112) and (113) planes was no greater than 2000 arcsec. The test results of the FWHM of the two crystal planes are shown in Table 3.

[0085] Table 3

[0086]

[0087]

[0088] Example 7

[0089] This embodiment relates to a method for characterizing the crystal quality of an 8-inch 3C-SiC epitaxial layer, which includes both a 4H-SiC substrate and 3C-SiC formed on the surface of the 4H-SiC substrate, and includes the following steps:

[0090] (1) The polished 3C-SiC epitaxial layer was placed on the sample stage of the X-ray diffractometer. The surface warp value of the polished 3C-SiC epitaxial layer was less than 20 μm.

[0091] (2) The full width at half maximum (FWHM) of the (112) and (113) crystal planes of the 3C-SiC epitaxial layer were obtained by nine-point X-ray diffraction tests. The incident angle of the (112) crystal plane was 11.1°, and the exit angle is shown in Table 4. The incident angle of the (113) crystal plane was 6.86°, and the exit angle is shown in Table 4. The scanning range of the (112) and (113) planes was no greater than 2000 arcsec. The test results of the FWHM of the two crystal planes are shown in Table 4.

[0092] Table 4

[0093]

[0094] According to the test results in Tables 3 and 4, when the incident angle of the (112) crystal plane is 10.6°±0.5°, the exit angle of the (112) crystal plane in Tables 1 and 2 is still within the range of 30.07°±0.5°. When the incident angle of the (113) crystal plane changes to 6.36°±0.5°, the exit angle of the (112) crystal plane in Tables 1 and 2 is still within the range of 35.87°±0.5°. Furthermore, for the same test object, the difference between the half-width at half maximum (WHM) of the (113) crystal plane and the (112) crystal plane is no greater than 40 arcsec, proving that the (112) and (113) crystal planes are highly accurate in testing crystal quality.

[0095] The above are merely embodiments of this application, and the scope of protection of this application is not limited to these specific embodiments, but is determined by the claims of this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the technical concept and principles of this application should be included within the scope of protection of this application.

Claims

1. A method for characterizing the crystallinity quality of a 3C-SiC epitaxial layer grown on a 4H-SiC substrate, characterized in that, Includes the following steps: (1) The polished 3C-SiC epitaxial layer is placed on the sample stage of an X-ray diffractometer. The surface warp value of the polished 3C-SiC epitaxial layer is less than 20 μm. The 3C-SiC epitaxial layer is a 3C-SiC epitaxial layer grown on a 4H-SiC substrate; (2) The half-width at half maximum (WHM) of the (112) and (113) crystal planes of the 3C-SiC epitaxial layer is obtained by X-ray diffraction test. When the difference between the WHM of the (113) crystal plane and the WHM of the (112) crystal plane is not greater than 40 arcsec, the WHM of the (112) crystal plane and the WHM of the (113) crystal plane are the crystal quality parameters of the 3C-SiC epitaxial layer. The scanning range of the (112) and (113) planes is not greater than 2000 arcsec.

2. The method according to claim 1, characterized in that, In step (2), the incident angle of the X-ray diffraction test on the (112) crystal plane of the 3C-SiC epitaxial layer is 10.6°±0.5° and the exit angle is 30.07°±0.5°.

3. The method according to claim 1, characterized in that, In step (2), the incident angle of the X-ray diffraction test on the (113) crystal plane of the 3C-SiC epitaxial layer is 6.36°±0.5° and the exit angle is 35.87°±0.5°.

4. The method according to claim 1, characterized in that, The diameter of the 3C-SiC epitaxial layer is 6 inches or more; and / or In step (2), at least 5 tests are performed on both the (112) and (113) crystal planes.

5. The method according to claim 4, characterized in that, The diameter of the 3C-SiC epitaxial layer is 8 inches or more.

6. A method for characterizing the crystallinity quality of a 3C-SiC substrate, characterized in that, Includes the following steps: (1) Place the polished 3C-SiC substrate on the sample stage of the X-ray diffractometer; (2) The half-width at half maximum (WHM) of the (112) and (113) crystal planes of the 3C-SiC substrate is obtained by X-ray diffraction test. When the difference between the WHM of the (113) crystal plane and the WHM of the (112) crystal plane is not greater than 40 arcsec, the WHM of the (112) crystal plane and the WHM of the (113) crystal plane are the crystal quality parameters of the 3C-SiC substrate.

7. The method according to claim 6, characterized in that, In step (2), the incident angle of the X-ray diffraction test on the (112) crystal plane of the 3C-SiC substrate is 10.6°±0.5° and the exit angle is 30.07°±0.5°.

8. The method according to claim 6, characterized in that, In step (2), the incident angle of the X-ray diffraction test on the (113) crystal plane of the 3C-SiC substrate is 6.36°±0.5° and the exit angle is 35.87°±0.5°.

9. The method according to claim 6, characterized in that, The surface warpage of the polished 3C-SiC substrate is less than 20 μm.

10. The method according to claim 6, characterized in that, The 3C-SiC substrate has a diameter of 6 inches or more; and / or In step (2), at least 5 tests are performed on both the (112) and (113) crystal planes.

11. The method according to claim 10, characterized in that, The diameter of the 3C-SiC substrate is 8 inches or more.